Productivity and Independence of Madrasah Ibtidaiyah Students Through Integrated Learning with Information and Communication Technology/ Produktivitas dan Kemandirian Siswa Madrasah Ibtidaiyah Melalui Pembelajaran Terintegrasi dengan Teknologi Informasi - Prasetiyo, Yoga Catur; Andi Prastowo (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2022)
The adaptation of online learning due to the impact of the coronavirus disease is facing various obstacles, including network restrictions, as well as lack of electronic means and the ability of parents to help children learn. Students who previously studied face-to-face should begin to adapt to learning by using information and communication technology. This study aims to determine the productivity and independence of students in learning activities integrated with the information and communication technology in the Madrasah Ibtidaiyah Abdul Barri. This study is a descriptive qualitative study. The data collection methods used were interviews and observation. Interviews were held with the director, teachers and guardians of students. The results of this study show that the productivity of students in computer-based learning activities is manifested in the activity of collecting student structured assignments using the information technology. Meanwhile, student independence can be measured through the completion of assignments and the submission of them in-hand to the teacher, without relying on parents’ aid, but remain under parental supervision. The computer-based learning as an extracurricular activity has the potential to stimulate the interests of students to use information and communication technology, and to expose them the benefits of the technology-based learning tools as an alternative to school-based learning in order to develop their productivity and independence. Abstrak Adaptasi pembelajaran daring akibat dampak virus corona memiliki berbagai hambatan, antara lain kendala jaringan, serta kurangnya fasilitas elektronik dan kemampuan orang tua dalam mendampingi anak belajar. Peserta didik yang tadinya melakukan pembelajaran tatap muka harus mulai beradaptasi pada pembelajaran dengan memanfaatkan teknologi informasi dan komunikasi. Penelitian ini bertujuan untuk mengetahui produktivitas dan kemandirian siswa dalam kegiatan pembelajaran yang terintegrasi dengan teknologi informasi dan komunikasi di Madrasah Ibtidaiyah (MI) Abdul Barri. Penelitian ini merupakan penelitian kualitatif deskriptif. Teknik pengumpulan data adalah wawancara dan observasi. Wawancara dilakukan kepada Kepala Madrasah, guru, dan wali siswa. Hasil penelitian ini menunjukkan bahwa produktivitas siswa dalam kegiatan pembelajaran berbasis komputer diukur dari keberhasilan pengumpulan tugas-tugas terstruktur siswa dengan memanfaatkan teknologi informasi. Sementara itu, kemandirian siswa terlihat pada aktivitas siswa mengerjakan tugas dan mengirimkannya kepada guru secara mandiri tanpa bantuan orang tua mereka, namun tetap dalam pengawasan orang tua. Pembelajaran komputer sebagai ekstrakurikuler mampu menumbuhkan rasa ingin tahu siswa terhadap terknologi informasi dan komunikasi serta mengenalkan siswa perangkat pembelajaran berbasis teknologi sebagai alternatif pembelajaran di sekolah untuk mengembangkan produktivitas dan kemandirian siswa.